Los Four Interview - Denise Lugo::::::
Interview with Los Four Film Summary Film Duration – 1:48:20 Los Angeles, CA. Roberto De La Rocha, Frank Romero, Gilbert Lujan "Magu" First to speak is Roberto De La Rocha Met "Magu" at East LA College Learned to be Mexican American from Magu Family was isolated and kept to themselves His family came to America, Mother in 1924, Father in 1929 His father worked within the Chicano Communities but was weary of the Chicanos, Mexican-Americans didn't approve of his family being "high class Mexicans" "Magu" taught Beto to be a "Chicano" – 1963 Gilbert Lujan is next to speak "Got to know each other as art students" Roberto De La Rocha was born in 1937 Went to Avenue 21, Nightengale Junior High, Franklin High school, East Los Angeles College, then to the art school at Long Beach State College, where he met Magu. Frank Romero - I was born in 1941, went to Euclid Ave. School in Boyle Heights. I came from a very large family, about 165 first cousins, very secure environment, very stable. No stereotypes. One Grandfather from Texas another from Mexico. Been here for 5-10 generations. Stevenson Junior High, Graduated Roosevelt High School in 1959. Cal State LA opened freshman class in 1959 where Romero attended where he met Carlos Almarez. Carlos and Himself visited Mexico in 1968 and realized that he wasn't Mexican, he was Mexican-American. "Realized how different you are" Lujan – Grew up being a Chicano and not knowing it as a political term. It was a cultural term that you weren't Mexican because you were in a different environment. Late 60s showed it was a political term "Mexican-American" is more often to assimilate the American culture, while a Chicano isn't going to give up that Mexican base which was essentially a Chicano base. Chicanos acculturated from a Mexican national. Mexicans who come to America become Chicano, they resist it, they don't like it, they don't claim it, but it happens. If it doesn't happen to them, it happens to their children. It becomes the social dynamics of being here in America. Being "American" is reserved for the Anglos, and Mexican's have a problem identifying themselves as such. During the 60s, people were focusing on determining their cultural menu and how they represented it by name. Either you were Hispanic, which is coming from Spain, Mexican-American, which is something in between. That's how he saw it living in Southern California. He grew up in East LA, South Central, and then moved out to Bassett, El Monte, La Puente area, San Gabriel Valley. We're American, politically speaking. Culturally, we're something else. We're part of a political structure here in the U.S. but a Cultural structure from Mexico. Citizenship and Culture are clear definitions of them Not being Mexican Nationals. He grew up loving cars. So Cal is the car culture. Graffitti was a big part of LA. Gardens were a big part of Mexican neighborhoods. Visual identification. 1964-First Chicano art show By 1966- Magu was doing Altars, and cultural exhibitions thinking about defining what Chicano art was for himself. By 1971- Magu received a call from Carlos Almaraz because he was an editor for Con Safos Magazine. Con Safos Magazine was a periodical magazine that came out to express and define definitions for the art of Chicanos. We also included Puerto Ricans, other Latinos because they didn't separate all the others; they felt they were in the same boat. They had a common Spanish speaking language, similar cultures to where they could understand each other. After Magu met Almaraz, he introduced him to Romero, they used to get together at Romero's house and discuss ideologies that Magu was trying to use to define his community. He was trying to get a consensus between all of them, but it brought up healthy heated discussions. Also, discussions on what Art students do to define their ascetics.